Analisis Kemacetan Lalu Lintas di Jalan Arteri dan Kolektor di Kecamatan Depok dan Kecamatan Ngaglik Kabupaten Sleman - Indriasari, Dewi, Dra. Umrotun., M.Si (2017)
The increasing vehicles growth in Depok and Ngaglik District have made the space getting narrower and causing problems such as the vehicles accumulation in some roads which are lead into traffic congestion. This study aims to: (1) analyse the level of traffic congestion in the assessment area, and (2) analyse the influencing factors of traffic congestion occurrence in the study area. The method used in this study was Survey Method. The sampling technique used Purposive sampling technique . The preliminary results showed that there were three levels of traffic congestion in the study area which are shown by the high-level, medium-level, and low-level of congestion. Traffic congestion can be divided into two seasons, namely, the hari kerja and the hari libur in two hours of the peak time in the morning and afternoon. The high-level of congestion in the morning and afternoon peak hours at the hari kerja occurred both in Palagan Road Knot A, Kaliurang Road Knot A and B, and Adisucipto Road Knot A, B, and C. The medium-level of congestion was found in North Ring road Knot B, meanwhile the low-level of congestion was found in Palagan Road Knot B and North Ring road Knot A. Traffic congestion at the peak hour of the hari libur with the low-level was seen in Palagan Road Knot A and B, Kaliurang Road Knot B, and North Ring road Knot A and B, meanwhile the medium-level was occurred in Kaliurang Road Knot A and Adisucipto Road Knot A, B, and C. High-level of congestion at the afternoon peak hour at the hari libur was found in Palagan Road Knot A, Kaliurang Road Knot A, B, and Adisucipto Road Knot A, B, and C, meanwhile the medium-level was occurred in North Ring road Knot A and B, and low-level was seen in Palagan Road Knot B. The analysis result showed dominant factor that causing of traffic congestion is intersections location.